1971
DOI: 10.1042/bj1250036pa
|View full text |Cite
|
Sign up to set email alerts
|

The development of hypoxanthine-guanine phosphoribosyltransferase activity in man

Abstract: PROCEEDINGS OF THE BIOCHEMICAL SOCIETY no inhibition with respect to hydroxylamine and non-competitive inhibition with respect to glutamate. It was also found that AMP is a powerful competitive inhibitor of the kidney enzyme with respect to hydroxylamine. The K, is approx. 1OuM. AMP does not affect the activity of muscle glutamine synthetase. Although it is difficult to interpret several of these observations, they underline further the-marked difference in properties between the enzymes from the two tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…guanosine phosphorylase (EC 2.4.2.15), inosine phosphorylase (EC 2.4.2.1) and adenosine deaminase (EC 3.5.4.4), although such methods have yielded useful results. The present method (Adams et al, 1971) and several subsequent methods have avoided these difficulties by inhibiting 5'-nucleotidase almost completely with 1.5mM-dTTP (Murray & Friedrichs, 1969;Fujimoto & Seegmiller, 1970).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…guanosine phosphorylase (EC 2.4.2.15), inosine phosphorylase (EC 2.4.2.1) and adenosine deaminase (EC 3.5.4.4), although such methods have yielded useful results. The present method (Adams et al, 1971) and several subsequent methods have avoided these difficulties by inhibiting 5'-nucleotidase almost completely with 1.5mM-dTTP (Murray & Friedrichs, 1969;Fujimoto & Seegmiller, 1970).…”
Section: Discussionmentioning
confidence: 95%
“…Radioautographic studies on the location of hypoxanthine/guanine phosphoribosyltransferase in the testes ofchildren showed that there was much activity throughout the sections, with the highest concentrations in the basal cells of the seminiferous tubules in the spermatogonia. Thyroid used as a control tissue showed virtually no activity (Adams, 1973). .-One foetal testis and a foetal ovary both showed .considerable activity, 203 and 130nmol/h per mg of protein rbspectively; but no activitywas,dettable in the ovary of a child aged 7, years.…”
Section: Erythrocyte Purine Phosphoribosyltransferase Activities In Manmentioning
confidence: 90%
“…The largest difference, which is that seen between basal ganglia and the cerebral cortex is only twofold (Kelley et al, 1969). This apparent difference may be further diminished when account is taken of the 5' nucleotidase (5' ribonucleotide phosphohydrolase EC 3.1.3.5) activity in different parts of the brain (Adams et al, 1971;Adams, 1973). Factors other than the absolute levels of HGPRT may be important in determining the evolution of brain damage in the Lesch-Nyhan syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotheses to explain hyperuricemia and the development of neurologic dysfunction have been examined in detail [10,37,44]. H-G PRT has high activity in fetal brain [1,39], and values rise to the higher values of adult brain shortly after birth [1]. Although enzyme activity is particularly high in basal ganglia [39], pathologic study of the central nervous system in autopsied cases does not reveal specific anatomic lesions [42,51].…”
Section: Discussionmentioning
confidence: 99%